Individual and dyadic coping in chronic pain patients - Burri, Andrea (J Pain Res, 2017)
The purpose of the current cross-sectional study was to test the associations between individual coping responses to pain, dyadic coping, and perceived social support, with a number of pain outcomes, including pain intensity, functional disability, and pain adjustment, in a sample of N = 43 patients suffering from chronic pain in Switzerland. In contrast to previous research, we were interested not only in specific pain coping but also in more general stress coping strategies and their potential influence on pain outcomes. Analyses were performed using correlation and regression analyses. “Praying and hoping” turned out to be an independent predictor of higher pain intensity and higher anxiety levels, whereas both “coping self-instructions” and “diverting attention” were associated with higher well-being, less feelings of helplessness, and less depression and anxiety. We further found a link between “focusing on and venting emotions” and “worse pain adjustment”. No significant relationship between dyadic coping and social support with any of our pain outcomes could be observed. Overall, our results indicate that individual coping strategies outweigh the effects of social support and dyadic coping on pain-related outcomes and pain adjustment. However, results need to be interpreted with caution given the small sample size.